Immunization Status of One- To Six-Year-Old Children Covered Under Integrated Child Development Scheme in Berhampur Municipal Area, Odisha - Mohapatra, Gurukrushna; Nayak, Lomapada; Karmee, Nivedita; Tripathy, R M (National Journal of Community Medicine, 2016)
Introduction: Immunization plays a key role in reducing the morbidity as well as mortality against the common preventable diseases of children. Even though the aim of the universal immunization programme is to provide 100 % coverage still there are many infants and children who are not protected against the killer diseases. As part of intersectoral co- ordination anganwadi centers under ICDS play an important role in immunization of children and pregnant women. The objective of the present study was to assess the immunization status of children 1-6years age group attending anganwadi centers (AWC). Methodology: It was a field based cross-sectional study. Sample size was calculated to be 384 and multistage sampling method was used to select the study population. Results: About 79% were from urban areas and 21% belonged to urban slums. Among them 52% were males. Vaccines coverage was highest for OPV zero dose i.e. 89% and 93% in ICDS project I and II respectively. The lowest coverage was found for Hepatitis B 3rd dose i.e. 63% as an average. Complete immunization of beneficiaries in areas where AWCs were functioning for more than 10years was about 73%. Conclusion: Immunization coverage of children attending AWCs was not adequate and needs further evaluation.